Types of Authentic Learning Assessment - Bayu Purbha Sakti (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2022)
Authentic assessment of learning cannot be done instantly. Teachers often underestimate authentic assessments that cover all areas of knowledge, attitudes and skills. The purpose of this study is to find out the discussion of the discussion and clarify the type of authentic assessment in learning activities. The researcher uses the library research method. Data analysis techniques used include data reduction, data display, and data verification. Assessment is one of the factors that determine the success of the learning process and results, not only as a way to assess the success of students. Authentic assessment is one of the methods used by educators in measuring the ability of students to achieve learning objectives used in learning activities. The types of authentic assessments that are often used are performance appraisals, written appraisals, project appraisals, and portfolio appraisals.